Increased physiological responsiveness to preferred music among young adults with autism spectrum disorders. (May 2016) - Hillier, Ashleigh; Kopec, Justin; Poto, Nataliya; Tivarus, Madalina; Beversdorf, David Q.
Individuals with autism spectrum disorders (ASD) experience high levels of anxiety and difficulty with emotion regulation and self-control. Music has been shown to modulate moods and emotions and may be useful in mediating individuals' physiological state. This study investigated whether listening to preferred self-selected music would have a significant physiological effect with regard to skin conductance responses, and also psychologically as measured by a self-report anxiety tool, among persons with ASD as compared to a matched control group. Results showed that participants with ASD were more responsive physiologically to their preferred music than those in the comparison group. They did not differ from controls in their responses to a piece of music previously demonstrated to induce feelings of relaxation among typical populations. Our findings indicate that persons with ASD are particularly responsive to the influence of music with regard to modulating their physiological state and this could potentially be a useful non-pharmacological tool for self-regulating emotional responses to stressors in their environment.